Estudo teórico de nanodomínios de grafeno e siliceno em carbeto de silício - Kremer, Luiz Felipe (2018)
In this work the structural, optical and electronic properties of hexagonal monolayer compounds of silicon carbide (h-SiC) in pristine form and in the presence of defects like graphene (h- SiC-C) and silicene (h-SiC-Si) nanodomains were studied. The physical properties of these nanostructures were obtained within the Density Funcional Theory framework as implemented in the SIESTA code, where the term of exchange-correlation energy is described by the GGA-PBE. To modulate the interactions between the valence electrons and the ionic core, norm conserved pseudopotencials were used, according the description of Troullier-Martins. The integration of the first Brillouin zone was done using special points generated by a 4 4 1 mesh within the Monkhorst-Pack scheme. The forces were minimized using the Hellmann-Feynman theorem until they are smaller than 0,05 eV/Å. The results show that these structures are metastable when compared with the bulk fases and have semiconductor character. In the presence of the nanodomains new electronic levels appear resulting in a small band gap. This occur due to the C-C bonds (for the h-SiC-C) and Si-Si bonds (for the h-SiC-Si), as can be seen in the projected density of states. The charge density isosurfaces show that for the h-SiC-C, in the nanodomain, the valence band minimum (VBM) has a bonding character and the conduction band maximum (CBM) has a anti-bonding character. The optical absorption coe cient was also calculated. In the pristine form was observed only a single absorption peak for photons parallely polarized to the plane of the h-SiC in the region of visible light. For the h-SiC-C were observed more absorption peaks in the visible light region. For the h-SiC-Si besides the absorption peaks for photons parallely polarized to the monolayer plane, were observed also peaks of absorption for photons perpendicularly polarized to the monolayer plane.